Implementasi Pendekatan Saintifik Pada Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Negeri 22 Kota Ternate - Bujuna Alhadad; Radjiman Ismail; Natsir Machmud (Jurnal Ilmiah Wahana Pendidikan, 2023)
The aim of the research was to find out how far the implementation of the scientific approach to the teaching of Islamic Religious Education in 22 Public Elementary Schools in the city of Ternate. This research is a descriptive qualitative research using a phenomenological method. Data analysis was carried out using qualitative techniques with the Miles and Huberman models. This is shown by the results of research during the composition of lesson plans for PAI in public elementary schools in 22 cities of Ternate which have achieved several successes from various points of view, namely the point of view of achieving learning objectives, the nature of activities expected in Islamic education learning. Then at the learning level sentence structure in accordance with the requirements of the scientific approach has been removed disassembled, even though there are no clearly visible performance indicators, and implemented, although some things are not in accordance with the concept of education and need more serious attention.